Pengaruh Pop Up Book Storytelling Berbasis Satua Bali untuk Meningkatkan Self Responsibility Anak Usia Dini - Arlina Laia; Putu Indah Lestari; Christiani Endah Poerwati (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2026)
The low level of self-responsibility character among early childhood learners, along with the challenges posed by rapid technological development affecting children’s behavior and social interaction, underlies this study. This research aims to determine the effect of implementing a storytelling method based on Balinese satua using pop-up book media on early childhood self-responsibility. The study employed a quasi-experimental design with a nonequivalent control group design. The subjects consisted of 72 children from Group B at PAUD Saraswati IV Denpasar, divided into 37 children in the experimental group and 35 children in the control group. Data were collected using observation sheets with self-responsibility indicators, including completing tasks, taking care of belongings, returning items to their original place, and respecting time and peers. Data analysis was conducted using normality tests, homogeneity tests, and ANOVA. The results showed that the data were normally distributed and homogeneous. The ANOVA test indicated a significance value of 0.000 (p < 0.05), which means there is a significant effect of the implementation of the storytelling method based on Balinese satua using pop-up book media on early childhood self-responsibility. The findings suggest that storytelling based on local wisdom, supported by pop-up book media, can enhance children's engagement in learning and effectively foster self-responsibility. Therefore, this method can be used as an alternative learning strategy to develop character in early childhood.